Bumpless‐transfer‐based fault tolerant control for the quadcopter: Piecewise homogeneous emission probability approach - Cai, Bo; Pei, Dacheng (International journal of robust and nonlinear control, 2024)
This paper investigates the fault‐tolerant control for quadcopter systems with the condition of reducing the bumps of system states. Allowing for the unavailable information of fault detection and identification (FDI) process in reality, a novel fault‐tolerant control scheme integrated with semi‐Markov stochastic process is considered, which stands in marked contrast to previous researches with the assumption of accurate FDI information. The emission probability satisfying piecewise homogeneous property is introduced to express the relationship between the obtained FDI information and real one, which covers more practical scenarios compared with existing ones. Afterwards, sufficient conditions on existence of the bumpless transfer controller reaching prescribed performance are obtained insuring that the quadcopter system is stable in the sense of mean square stability (MSS) and capable of dealing with the unavoidable bumps of states caused by stochastic switching dynamics. Eventually, simulations and comparative studies are performed to illustrate the advantages of the proposed strategy.